A TRIBUTE TO PROF. DR. LAMBERTUS JOHANNES TOXOPEUS, A CENTURY OF APPRECIATION - Tati Suryati Syamsudin; Djunijanti Peggie; W. John Tennent; Djoko Iskandar (BRIN Publishing (Penerbit BRIN), 2025)
Prof. Dr. Lambertus Johannes Toxopeus, a Dutch entomologist, was born, worked, and died in Indonesia. He was a Lepidoptera specialist and has published 68 papers, describing two tribes, five subtribes, 26 genera and 147 butterfly species or subspecies between 1922-1951. We gleaned from the literature that he was honored hi eponyms in one family, seven genera and at least 169 species or subspecies, mostly arthropods, but also a reptile, birds, mammals, mollusks, and plants. This represents an average of one to two species named after him every year during the last 100 years, mostly collected by himself from very fruitful expeditions throughout Sundaland, Buru Island and the highland of Papua Province, Indonesia. His work contributed significantly to knowledge of on Southeast Asian biodiversity.